Field programmable gate array‐based control method for a pulse density modulated microinverter operating in island mode. Issue 14 (1st November 2016) - Korošec, Lucijan; Konjedic, Tine; Truntič, Mitja; Rodič, Miran; Milanovič, Miro
Abstract : This study proposes a new control method for a pulse‐density modulated microinverter and its implementation within a field programmable gate array circuit. The structure and operating principle of the studied microinverter demand implementation of a pulse‐density modulation‐based control method with two independent control loops. The first one ensures a constant input current from the source while the second one provides a sinusoidal voltage at the converter's output. At the same time the implemented control method ensures zero‐current switching of the utilised power transistors in decoupling and output stages which allows operation at high switching frequency. The performance of the proposed control method for a microinverter operating in island mode was experimentally verified in steady‐state operation, as well as during load transients.